2017
DOI: 10.1111/jgs.14997
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Alzheimer's Disease: Lessons Learned and Applied

Abstract: Alzheimer’s disease (AD) affects over 5 million Americans with substantial consequences to patients, families and society that will only continue to be a significant cause of morbidity, mortality, and healthcare costs. With disease-modifying treatment trials unsuccessful at the present time and only symptomatic medications available, an emerging approach is the creation of prevention trials. Advances in diagnostic criteria, biomarker development and improved understanding of the biophysiological basis of AD ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 29 publications
0
67
0
Order By: Relevance
“…Furthermore, this asymptomatic stage might be the only window of opportunity for antiamyloid therapies, which have failed to slow the progression of cognitive symptoms significantly, in individuals with symptomatic or prodromal AD. Better identification of individuals at risk of dementia might also be of great interest for intervention trials aiming to delay the onset of clinical symptoms …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this asymptomatic stage might be the only window of opportunity for antiamyloid therapies, which have failed to slow the progression of cognitive symptoms significantly, in individuals with symptomatic or prodromal AD. Better identification of individuals at risk of dementia might also be of great interest for intervention trials aiming to delay the onset of clinical symptoms …”
Section: Discussionmentioning
confidence: 99%
“…We have now shown that optimised and targeted interventions can help to address the underlying causes of cognitive decline. The role of neurotoxins, nutritional deficiencies, inflammation and the gut microbiome in neurodegenerative disease (Bland, 2016) can lead to a personalised care plan and enhanced precision of treatment decisions (Galvin, 2017). Moreover, a person's dementia has a unique etiology which must be understood individually to develop personalized treatment (Pomorska & Ockene, 2017).…”
mentioning
confidence: 99%
“…Cognitive interventions at the preclinical phases could be beneficial in delaying the onset of cognitive impairment [17][18][19]. Randomized control trials (RCTs) have offered some short-term impact of interventions that can improve cognitive function such as dance [20], exercise [21], physical activities [22], and psychological intervention [23].…”
Section: Introductionmentioning
confidence: 99%